Bearheart : The Heirship Chronicles - Vizenor, Gerald Robert, 1934- (Book collections on Project MUSE., 1990)
Bearheart, Gerald Vizenors first novel, overturns "terminal creeds" and violence in a decadent material culture. American civilization has collapsed and Proude Cedarfair, his wife, Rosina, and a bizarre collection of disciples, are forced on a pilgrimage when government agents descend on the reservation to claim their sacred cedar trees for fuel. The tribal pilgrims reverse the sentiments of Manifest Destiny and travel south through the ruins of a white world that ran out of gas.